Pluralism, Transnationalism and Culture in Asian Law A Book in Honour of M.B. Hooker. - Bell, Gary F. ([S.l.] : ISEAS - Yusof Ishak Institute, 2017)
To honour this great scholar, this book gathers essays from admirers and friends who add their own contributions on legal pluralism, transnationalism and culture in Asia. The book opens with an account of M.B. Hooker colourful and prolific career. The authors then approach legal pluralism through legal theory, legal anthropology, comparative law, law and religion, constitutional law, even Islamic art, thus reflecting the broad approaches of Professor Hooker's scholarship. While most of the book focuses mainly on Southeast Asia, it also reaches out to all of Asia up to Israel, and even includes a chapter comparing Indonesia and Egypt.
Pluralism, Transnationalism and Culture in Asian Law: A Book in Honour of M.B. Hooker -- Dedication -- Contents -- Preface -- Acknowledgements -- About the Contributors -- 1. M.B. Hooker and Southeast Asian Law: Path-breaking Passions -- 2. Asian Thought and Legal Diversity -- 3. Comparative Law, Anti-Essentialism and Intersectionality: Reflections from Southeast Asia in Search of an Elusive Balance -- 4. Legal Pluralism and Legal Anthropology: Experiences from Indonesia -- 5. Mapping the Relationship of Competing Legal Traditions in the Era of Transnationalism in Indonesia -- 6. Indonesia's Weak State Courts and Weak Law Fare Poorly in a Pluralist Commercial World -- 7. When Laws Are Not Enough: Ethics, Aesthetics, and Intra-Religious Pluralism in Contemporary Indonesia -- 8. Legal Pluralism and the Constitutional Position of East Malaysia's Indigenous Peoples: The View from the Longhouse -- 9. Sharia, State and Legal Pluralism in Indonesia: How Law Can You Go? -- 10. Negotiating Legal Pluralism in Court: Fatwa and the Crime of Blasphemy in Indonesia -- 11. Islamic Law in Israel: A Case Study in Legal Pluralism -- 12. The Road to Democracy Goes through Religious Pluralism: The Indonesian Case and Thoughts on Post-Mubarak Egypt.
Includes bibliographical references and index.
Keywords: Law